2021
DOI: 10.21608/aadj.2021.163879
|View full text |Cite
|
Sign up to set email alerts
|

Study the Effect of Two Different Types of Attachment Systems on strain of Mandibular complete Overdentures Retained by Midline Implant

Abstract: Aim: This study was conducted to evaluate the effect ball and equator attachments strain (invitro study) of mandibular over denture retained by single midline implant for completely edentulous patient. Subjects and methods: Ten complete lower dentures have ball attachment and another ten complete lower dentures have equator attachment were constructed on ten acrylic models covered by rubber material to simulate oral mucosa have single midline implant, strain were evaluated around the mandibular midline implant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…Higher MBLC in Group 3 might be relate to the ball attachment, the higher profile attachment when compared with OT Equator ® . These results were supported by Salem et al 31 reported the significant greater strain in ball attachment than OT Equator ® . The more resilience in OT Equator ® allowed the more movement in denture and…”
Section: Patient Satisfactionsupporting
confidence: 67%
“…Higher MBLC in Group 3 might be relate to the ball attachment, the higher profile attachment when compared with OT Equator ® . These results were supported by Salem et al 31 reported the significant greater strain in ball attachment than OT Equator ® . The more resilience in OT Equator ® allowed the more movement in denture and…”
Section: Patient Satisfactionsupporting
confidence: 67%